2011
DOI: 10.1093/icvts/ivr119
|View full text |Cite
|
Sign up to set email alerts
|

Policies of withholding and withdrawal of life-sustaining treatment in critically ill patients on cardiac intensive care units in Germany: a national survey

Abstract: This survey is a step towards creating standards of end-of-life care in cardiac ICUs, which may contribute to build consensus and avoid conflicts among caregivers, patients and families at each step of the decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
(41 reference statements)
0
10
0
8
Order By: Relevance
“…A summary of all included articles and their quality assessments are shown in (see Tables 1 , 2 , and 3 ). In total, eight articles were assessed as having either moderate-to-high or high quality, eight articles were assessed as having moderate quality, four articles were assessed as having low-to-moderate quality, and four articles were assessed as having low quality (reference [ 33 , 34 , 38 , 40 ]) (see additional file 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…A summary of all included articles and their quality assessments are shown in (see Tables 1 , 2 , and 3 ). In total, eight articles were assessed as having either moderate-to-high or high quality, eight articles were assessed as having moderate quality, four articles were assessed as having low-to-moderate quality, and four articles were assessed as having low quality (reference [ 33 , 34 , 38 , 40 ]) (see additional file 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…(2012) [ 33 ] European countries (6 countries) To examine whether religion and religiosity are important to end-of-life decisions and patient autonomy in the ICU Structured questionnaires in 6 European countries, 143 ICUs 304 physicians 6 Schimmer et al . (2012) [ 34 ] Germany To determine the decision-making process of withholding and/or withdrawing of life-sustaining treatment in cardiac ICUs in Germany Questionnaire distributed to all heart surgery ICUs ( N = 79) in Germany 35 clinical directors, 25 senior ICU physicians 6 Kübler et al . (2011) [ 35 ] Poland To analyse the attitudes of ICU physicians regarding decisions to forgo life-sustaining treatment for adult ICU patients Survey 217 intensive care physicians working in ICUs in Poland 6 Weng et al .…”
Section: Resultsmentioning
confidence: 99%
“…Medium-strength evidence was found that physicians prefer their own ideas of what is in the best interest of the patient, focusing instead on clinical and technical parameters to decide on withholding or withdrawing therapy, and do not respect the wishes of the patient or the patient’s family to stop therapy, even when there is a living will [ 27 , 33 , 34 , 40 ]. Further, medium-strength evidence was found for the barrier that, even when the team confirms that treatment is futile and inappropriate, physicians follow the family’s wishes when the family wants to continue futile treatment out of concerns about legal action [ 16 , 26 , 36 , 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such difficulties arise, in part, because a family may be facing an unexpected poor prognosis associated with an acute illness or exacerbation and, in part, because the ICU orientation is one way of saving lives. In a study of policies of withholding and withdrawal of life-sustaining treatment in critically ill patients on cardiac ICUs, cranial computed tomography with poor prognosis, multiorgan failure, and failure of assist device therapy were the most frequently cited medical reasons for withholding or withdrawal of life-sustaining treatments, while poor expected quality of life, the patient's willingness to limit medical care, and the family's choice were the top ethical reasons [11]. Unfortunately, a considerable variation in the apparent willingness of consultants to make endof-life decisions has been reported, emphasizing the subjective nature of these decisions [6].…”
Section: Key Pointsmentioning
confidence: 99%